Model Pengembangan Teori Islamic Corporate Governance - Ujang Syahrul Mubarrok; Muhamad Wahyudi; Izzani Ulfi (ITB AAS INDONESIA Surakarta, 2020)
Corporate governance becomes an interesting discussion when financial crisis occurs caused by financial scandals in 1980. Since then, many corporate governance concepts have emerged, including the concept of Islamic corporate governance (ICG). However, ICG research is still limited to the discussion of methodology development science. This study attempts to explain the development model of Islamic corporate governance theory by using the literature review method. The result of this study indicates that the development model of Islamic corporate governance theory can use a non-modification model that comes from the teachings of Islam and non-modification model that combines various sources.